2021
DOI: 10.1038/s41598-021-93671-1
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory role of Parkinson’s disease 7 in inflammatory bowel disease

Abstract: Recently the role of Parkinson’s disease 7 (PARK7) was studied in gastrointestinal diseases, however, the complex role of PARK7 in the intestinal inflammation is still not completely clear. Expression and localization of PARK7 were determined in the colon biopsies of children with inflammatory bowel disease (IBD), in the colon of dextran sodium sulphate (DSS) treated mice and in HT-29 colonic epithelial cells treated with interleukin (IL)-17, hydrogen peroxide (H2O2), tumor necrosis factor (TNF)-α, transformin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 54 publications
0
15
1
Order By: Relevance
“…Similarly, an autosomal recessive gene associated with early Parkinsonism, DJ-1 (PARK 7), is dysfunctional in human colonic tissue samples as well as in in vitro and in vivo experimental models of colitis (Zhang et al, 2020). As both IBD and PD have compromised intestinal barrier functions, DJ-1 deficiency promotes cytokinemediated inflammation (IL-1β, IL-6, TNFα, and TGFB1) and apoptosis of intestinal epithelial cells via a p53-dependent mechanism in vitro, in ex vivo colonic sacs, and in vivo (van IJzendoorn and Derkinderen, 2019; Zhang et al, 2020;Lippai et al, 2021). This further supports the hypothesis that the onset, progression and severity of IBD and PD are aggravated by geneenvironment interactions occurring at both the host and gut microbiome levels.…”
Section: Chronic Gut-inflammation and Intestinal Barrier Dysfunction ...mentioning
confidence: 99%
“…Similarly, an autosomal recessive gene associated with early Parkinsonism, DJ-1 (PARK 7), is dysfunctional in human colonic tissue samples as well as in in vitro and in vivo experimental models of colitis (Zhang et al, 2020). As both IBD and PD have compromised intestinal barrier functions, DJ-1 deficiency promotes cytokinemediated inflammation (IL-1β, IL-6, TNFα, and TGFB1) and apoptosis of intestinal epithelial cells via a p53-dependent mechanism in vitro, in ex vivo colonic sacs, and in vivo (van IJzendoorn and Derkinderen, 2019; Zhang et al, 2020;Lippai et al, 2021). This further supports the hypothesis that the onset, progression and severity of IBD and PD are aggravated by geneenvironment interactions occurring at both the host and gut microbiome levels.…”
Section: Chronic Gut-inflammation and Intestinal Barrier Dysfunction ...mentioning
confidence: 99%
“…The role of MMP-3 was also suggested in the proteomic cleavage and degradation of PARK7/DJ-1 in CATH neuronal cells [ 93 ]. Our very recent results showed that inflammatory mediators of IBD, including LPS, TNF-α, and TGF-β, decreased the expression of PARK7/DJ-1 in HT-29 colonic adenocarcinoma cells [ 11 ].…”
Section: Park7/dj-1mentioning
confidence: 99%
“…The role of cellular homeostasis regulator cell cycle autoantigen (SG2NA) has also been demonstrated to increase the expression of PARK7/DJ-1 by inhibiting its proteasome-mediated degradation in Neuro2a neuroblastoma cells [ 98 , 99 , 100 ]. Finally, our recent study showed that IL-17 and hydrogen peroxide increases the expression of PARK7/DJ-1 [ 11 ]. Interestingly, while increased oxidative stress is one of the main mediators of proteomic degradation of PARK7/DJ-1, our results showed that as a positive feedback mechanism it can facilitate its synthesis [ 11 ].…”
Section: Park7/dj-1mentioning
confidence: 99%
See 2 more Smart Citations